Methodological approach to the integral assessment of the regional lands use territorial development - Mamonov, Kostiantyn (Geodesy and Cartography, 2019)
The relevance of the research topic is caused by the need to ensure the territorial development of land use at the regional level. In this context, it is necessary to form a quantitative basis for assessing territorial development, which will make decisions in the field of land use and ensure the growth of land use efficiency in the region, considering spatial, urban planning, ecological and investment areas. As a result of the study, a methodological approach to the integrated assessment of the territorial development of land use in the region has been proposed. Its development is based on the application of principles and includes a set of interrelated stages. It was established that the formation of a complex of spatial, urban planning, investment, and ecological factors, which influence the territorial development of land use in the region is carried out on the basis of the analysis and systematization of existing scientific and methodological developments and regulatory support. An algorithm for the development and implementation of a methodological approach to an integrated assessment of the territorial development of land use in the region is proposed. It forms a closed system, which allows to develop and implement a methodological approach by applying of information support, appropriate methods and models to achieve a result on the growth of the integral indicator of land use in the region, considering spatial, urban planning, investment, and ecological characteristics. Based on the developed method, an estimated basis for the territorial development of land use in the region, adoption of justified decisions, regarding the formation and implementation of spatial, urban planning, investment, and ecological areas is created.